DNA METHYLATION IN THYROID-STIMULATING HORMONE GENE: PREDICTOR OF GRAVE’S DISEASE RECURRENCE IN INDONESIA - Luluk yunaini; Dwi Anita Suryandari; Trisia Lusiana Amir; Dwi Yanti; Fatimah Eliana (Journal of Global Pharma Technology, 2018)
Thyroid-stimulating hormone receptor (TSHR) has a critical role in Graves’ disease (GD). GD is an autoimmune disease which is multifactorial. Environmental factors can affect the epigenetic, a changes in gene expression without any changes in base sequence of the DNA. One of the epigenetic types is methylation. This study aims to determine the status of DNA methylation in TSHR gene in patients with GD to be one of the predictors of recurrence. This study used a case control design with 58 samples of GD patients divided into 29 groups of recurrence and 29 groups of non-recurrence. DNA methylation examination used methylation-specific PCR (MSP) method. Our result found that DNA methylation profile of GD in Indonesia were 5% with complete DNA methylation, 17% complete DNA unmethylation and 78 partial DNA methylation. Statistical analysis showed no significant different between recurrence and non-recurrence group (p>0.05). Nevertheless, our result showed no patient with complete status DNA methylation was found in recurrence group. This shows that in recurrence occur a reduction of DNA methylation resulting in increasing of TSHR production. Thus, DNA methylation in TSHR gene might be has a role in the risk of recurrence GD.